Concept analysis of perceived health from the perspective of rural adults in China. Issue 2 (5th June 2021) - Tang, Yafen; Ye, Jing; Yang, Lili; Ran, Lulu; Wu, Jingjie
Abstract: Purpose: This paper aims to clarify the concept of perceived health from the perspective of rural adults in China. Methods: Walker and Avant's concept analysis was applied. Findings: Perceived health from rural adults in China is a subjective assessment of their health status, which is deeply affected by Chinese traditional culture and being in a rural environment. Conclusions: Most rural adults in China could perceive their health as good or poor, however, rural areas have disadvantages in health care, geographical location, and educational resources compared with urban counterparts, which may lead to some unscientific health attitudes and lifestyles and hinder their healthcare‐seeking behaviors. Implication for Nursing Practice: To help nurses understand better the concept of perceived health with the rural background, which is different from urban areas. Perceived health provides rich information resources for nurses to carry out holistic care, and to lead rural adults in China to form a correct and positive attitude and lifestyle as possible.